Somatosensory coding of visual self-identity - Mattia Galigani; Marcella Romeo; Nicoletta Scanferlato; Massimiliano Valeriani; Bettina Forster; Francesca Garbarini (NeuroImage, 2025)
How does the brain process our bodily identity? This question has long fascinated scientists because of its potential implications for the study of self-awareness. Here, to test the idea that the somatosensory system is directly involved in coding bodily self-identity even when conveyed through vision, we probed the somatosensory system with tactile stimuli while participants observed hand images, either belonging to them (self-hand) or to another person (other-hand). In three psychophysical experiments (discovery, replicating and control samples), we found faster reaction times to tactile stimuli when paired with the self- than the other-hand image. To explore the neural basis of this effect, we conducted two electrophysiological experiments (discovery and replicating samples), and we observed that visual activity did not vary as a function of bodily identity, whereas the activity of the primary (at around 40 ms) and secondary (from 100 ms) somatosensory cortices did vary, as revealed by significantly higher somatosensory responses to tactile probes when presenting the self- than the other-hand image. We propose that this somatosensory coding of visual self-identity may be the result of associative learning mechanisms, through which individuals learn that the association between visual and somatosensory input only pertains to the own body, thus representing a possible prerequisite for establishing self-awareness.